2005
DOI: 10.1002/pbc.20466
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcomas utilize developmental, myogenic growth factors for disease advantage: A report from the children's oncology group

Abstract: Increased transcriptional levels of PDGF receptors and insulin-like growth factor are associated with decreased survival in rhabdomyosarcomas. Dual blockade of these growth-factor-signaling pathways may be a valuable strategy in preclinical therapeutic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 41 publications
3
67
0
1
Order By: Relevance
“…It has also been reported that both VEGF and PDGF families are involved in neo-angiogenesis in embryos and tumors (84). RMSs have been reported to express IGF and PDGF receptors (6). However, receptor expression is independent of signal molecule expression.…”
Section: Cytokine/cytokine Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that both VEGF and PDGF families are involved in neo-angiogenesis in embryos and tumors (84). RMSs have been reported to express IGF and PDGF receptors (6). However, receptor expression is independent of signal molecule expression.…”
Section: Cytokine/cytokine Interactionsmentioning
confidence: 99%
“…However, receptor expression is independent of signal molecule expression. The expression of PDGF has been associated with poor prognosis (6). MET is the receptor of the hepatocyte growth factor (produced by bone marrow stromal cells) (85) specific for the acute phase of T-ALL (86).…”
Section: Cytokine/cytokine Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 One group evaluated platelet-derived growth factor receptor (PDGFR) gene expression in pediatric rhabdomyosarcoma and demonstrated decreased failure-free survival for patients with tumors that overexpressed either PDGFR-a or PDGFR-b mRNA. 17 Several mediators of extracellular matrix breakdown have been shown to correlate with prognosis in patients with soft-tissue sarcoma. Increased levels of matrix metalloproteinase-2 (MMP-2), MMP-9, and urokinase plasminogen activator appear to confer a worse prognosis, whereas increased levels of tissue inhibitor of metalloproteinase-2 (TIMP-2) are associated with improved outcomes.…”
Section: Soft-tissue Sarcomamentioning
confidence: 99%
“…Hh signaling is known to regulate multiple aspects of normal myogenesis, including the initiation and maintenance of MyoD family expression, the development, survival and proliferation of the epaxial and hypaxial muscle lineages, and the selection of muscle fiber type (Munsterberg et al, 1995;Borycki et al, 1999;Kruger et al, 2001). Moreover, elevated Hh signaling has recently been observed in sporadic cases of embryonal rhabdomyosarcoma (Blandford et al, 2006;Tostar et al, 2006), in addition to the rhabdomyosarcoma formation that is associated with Ptch1 haploinsufficiency. However, a precise mechanistic understanding of how the Hh signal modulates normal skeletal muscle development and promotes rhabdomyosarcoma formation does not exist.…”
Section: Introductionmentioning
confidence: 99%